(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Particularly in regions with diverse economic landscapes such as Uttar Pradesh, the business environment stands as a crucial determinant for the sustainability and success of small enterprises. The objective of this research is to investigate the impact of the legal framework, economic conditions, and socio-cultural factors on shaping the business environment in Uttar Pradesh, with a specific focus on small businesses. A comprehensive understanding of the intricate dynamics within Uttar Pradesh’s small industry sector and the broader business climate is essential for policymakers, business owners, and stakeholders. This knowledge can empower them to implement targeted interventions and initiatives, fostering a conducive environment for small businesses in the area. The study delves into the role of the business environment in contributing to Uttar Pradesh’s 5 trillion share in India’s GDP. Various aspects, including political stability, market dynamics, global integration, human capital, infrastructure development, regulatory adjustments, and environmental sustainability, are examined to elucidate their significance in cultivating a favourable business climate.